Implementation of learning analytics in primary and secondary school: a systematic literature review - Abdullah, Samsu Hilmy; Mohd Puad, Mohd Hazwan; Azmi Murad, Masrah Azrifah; Murad, Erzam Marlisah (Human Resource Management Academic Research Society, 2022)
Increased adoption of educational technologies, the emergence of digital classroom concepts, and the interest in big data innovations have led to a growing awareness of the potential implementation of learning analytics to support learning development in educational institutions. However, most studies have focused on the implementation of learning analytics in higher education. As a result, research evidence and studies on actual and ongoing implementation in pre-higher education are still scarce. Therefore, there is a need to understand better the implementation of learning analytics at primary and secondary from the current learning analytics literature. This systematic literature review (SLR) aimed to identify learning analytics research that focuses on implementing learning analytics at pre-higher education levels, including in pre-school, primary, or secondary school. This SLR was carried out based on the SALSA framework to determine the protocol, search, appraisal, synthesis, analysis, and reporting approaches. The findings of the SLR support the arguments that the implementation of learning analytics in school is still in its infancy, where the implementation has been observed mostly in developed countries. Most of the Implementation is aimed at descriptive analytics, focusing on the purpose of monitoring, analysis, and feedback. The literature review has shown a lack of research on the implementation of learning analytics at the primary and secondary education levels.